Types of Thyatirinae (Lepidoptera: Drepanidae) in the collection of the Zoological Institute of the Russian Academy of Sciences - Mironov, Vladimir G.; Zolotuhin, Vadim V. (Zootaxa, 2019)
The article deals with 14 taxa of the Thyatirinae moths, the types of most of which are kept in the collection of the Zoological Institute of the Russian Academy of Sciences (St. Petersburg). It is shown that the designation of lectotypes/holotypes of Thyatira hedemanni Christoph, 1885, Asphalia nigrofascicula Graeser, 1888, and Cymatophora or var. terrosa Graeser, 1888, by Laszlo & al. (2007) on the basis of specimens preserved in the collections of Berlin and London Museums was based on non-syntypic specimens, and that their designation as lectotypes needs to be corrected. Correct lectotypes are designated here for the taxa listed above as well for Gonophora dieckmanni Graeser, 1888, and Thyatira moellendorfi Fixsen, 1887; a lectotype of Cymatophora octogesima var. caucasica Krulikowsky, 1901, is designated from the collection of Kiev University. The following type localities are thereby fixed: Lagodekhi [Georgia] for Thyatira hedemanni Christoph, 1885, Pung Tung [Central Korea] for Thyatira moellendorfi Fixsen, 1887 and for Thyatira violacea Fixsen, 1887, Nikolaevsk-na-Amure [Far East of Russia] for Cymatophora or var. terrosa Graeser, 1888.